“Hoje, se espremer o espelho, sai sangue” : etnografia da produção de notícias de feminicídio para o telejornal JPB 1º edição (PB) - Paz, Pedro Henrique Gomes da (2018)
This paper aims to present the production of news about possible crimes of feminicide for the local and evening news TV JPB 1st Edition (PB), from TV Cabo Branco, an affiliate of Rede Globo in João Pessoa. It draws inspiration from the theories of journalism, especially Newsmaking, which articulates within the limits of journalists' professional culture and the organization of work and production processes (Wolf, 2005: 188). Based on the Map of Violence 2015 - Homicides of Women in Brazil and the project "Monitoring journalistic coverage on feminicide and sexual violence against women", from the Patrícia Galvão Mídia e Direitos Institute, which began in October 2015 and analyzed a total of 3,440 news published in 71 vehicles from all regions of the country, the methodological procedures of ethnography, of the type participant observation, of the daily life of the professionals, were carried out during two months, from 04/04 to 06/06 of 2017, from Monday to Friday, from 8 am to 2 pm and in-depth interviews with six journalists. During the period under review, seven news reports of likely femicides reported on television news items were identified. In general, journalists are unaware of the existence and distinction of the crime of feminicide, predicted since 2015, by Brazilian legislation. This misinformation guides the whole news process.